Semantically meaningful sample databases for constraint verification : a thesis presented in partial fulﬁlment of the requirements for the degree of Doctor of Philosophy in Computer Science at Massey University, Manawatu, New Zealand - Ye, Wendy (Weimin) (Massey University, 2026)
To ensure high-quality relational database design, theoretical developments are crucial, particularly in measuring constraints. Keys, functional dependencies (FDs), and inclusion dependencies (INDs) play pivotal roles and are practical for conveying data semantics in relational databases. However, ensuring the validity of constraints can be challenging when specified manually or mined from existing database instances. Example databases serve as valuable tools for inspecting the properties of proposed designs. Known in the literature as Armstrong databases, these databases precisely adhere to a specified set of dependencies and their logical consequences, excluding any additional dependencies not implied by them. Research efforts have focused on proving the existence and exploring the structure of Armstrong databases. The size of Armstrong databases is equally important; larger databases can be impractical as overlooked constraints become harder to detect. Moreover, when NULL values are involved, constructing Armstrong databases becomes more complex, requiring additional steps. Therefore, constructing a compact Armstrong database is challenging but essential for practical utility. Our study aims to improve existing methods by investigating and constructing Armstrong databases from scratch. This includes adapting existing real-world databases into Armstrong databases to enhance their utility and effectiveness in practical applications. By focusing on reducing the size of Armstrong databases, we aim to streamline the process of constraint validation and database design optimization. This research contributes to advancing the field by addressing the practical challenges of database constraint management and fostering the development of more efficient and reliable relational database designs.
Keywords: Compact Armstrong Database Construction; Relational databases; Design; Management; Databases; Semantics; Semantic computing; 460503 Data models, storage and indexing